Proceedings of the 2nd International ICST Conference on Performance Evaluation Methodologies and Tools 2007
DOI: 10.4108/valuetools.2007.1817
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Non-Ergodic Simulation Models of Logistics Networks

Abstract: Simulation is a frequently applied method when analysing logistics networks. Also within the Collaborative Research Center 559 "Modelling of Large Logistics Networks" simulation is broadly applied and process chains are used as a mutual basis for model development and description. Previous research activities exposed non-ergodicity of models as one of the typical application-specific problems which are difficult to discover by simulation.In order to detect non-ergodic models the problem has been reduced to its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
2
1
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…In particular, we will try to apply techniques such as Petri nets [2] and model checking [6] to formally understand and describe the possible dynamics of the system.…”
Section: Conclusion and Research Directionsmentioning
confidence: 99%
“…In particular, we will try to apply techniques such as Petri nets [2] and model checking [6] to formally understand and describe the possible dynamics of the system.…”
Section: Conclusion and Research Directionsmentioning
confidence: 99%
“…In the ProC/B toolset PN techniques [19] are used to analyze functional and non-functional properties. Classical PN techniques allow one to analyze properties such as deadlocks or liveness of a system and recently we developed an additional PNbased technique to detect non-ergodic models [20]. All of these, usually undesired, properties of a model are often difficult to detect with simulation.…”
Section: Non-simulative Analysismentioning
confidence: 99%
“…The philosophy of ProC/B is to describe system behaviour by process chains and system structure by functional units. Figure 2 and Figure 3 present a typical example of a ProC/B model [3]. The model is hierarchical and represents a freight village.…”
Section: Proc/bmentioning
confidence: 99%
“…In the course of the Collaborative Research Centre 559 "Modelling of Large Logistics Networks" (CRC 559; [1,2]) we made the experience that during the construction of a simulation model several interim versions of the model do not correctly reflect the system behaviour. We found that various discrepancies between the system and the model can be discovered by investigating functional properties [1,3,4]. An example is the occurrence of (partial) deadlocks in the simulation model which do not appear in the real system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation